A Pilot Study on the Association of Mitochondrial Oxygen Metabolism and Gas Exchange During Cardiopulmonary Exercise Testing: Is There a Mitochondrial Threshold? - Baumbach, Philipp; Schmidt-Winter, Christiane; Hoefer, Jan; Derlien, Steffen; Best, Norman; Herbsleb, Marco; Coldewey, Sina M. (Frontiers in Medicine, 2020)
Background: Mitochondria are the key players in aerobic energy generation via oxidative phosphorylation. Consequently, mitochondrial function has implications on physical performance in health and disease ranging from high performance sports to critical illness. The protoporphyrin IX-triplet state lifetime technique (PpIX-TSLT) allows in vivo measurements of mitochondrial oxygen tension (mitoPO2). Hitherto, few data exist on the relation of mitochondrial oxygen metabolism and ergospirometry-derived variables during physical performance. This study investigates the association of mitochondrial oxygen metabolism with gas exchange and blood gas analysis variables assessed during cardiopulmonary exercise testing (CPET) in aerobic and anaerobic metabolic phases. Methods: Seventeen volunteers underwent an exhaustive CPET (graded multistage protocol, 50 W/5 min increase), of which 14 were included in the analysis. At baseline and for every load level PpIX-TSLT-derived mitoPO2 measurements were performed every 10 s with 1 intermediate dynamic measurement to obtain mitochondrial oxygen consumption and delivery (mitoV.O2, mitoD.O2). In addition, variables of gas exchange and capillary blood gas analyses were obtained to determine ventilatory and lactate thresholds (VT, LT). Metabolic phases were defined in relation to VT1 and VT2 (aerobic: <VT1, aerobic-anaerobic transition: ≥VT1 and <VT2 and anaerobic: ≥VT2). We used linear mixed models to compare variables of PpIX-TSLT between metabolic phases and to analyze their associations with variables of gas exchange and capillary blood gas analyses. Results: MitoPO2 increased from the aerobic to the aerobic-anaerobic phase followed by a subsequent decline. A mitoPO2 peak, termed mitochondrial threshold (MT), was observed in most subjects close to LT2. MitoD.O2 increased during CPET, while no changes in mitoV.O2 were observed. MitoPO2 was negatively associated with partial pressure of end-tidal oxygen and capillary partial pressure of oxygen and positively associated with partial pressure of end-tidal carbon dioxide and capillary partial pressure of carbon dioxide. MitoD.O2 was associated with cardiovascular variables. We found no consistent association for mitoV.O2. Conclusion: Our results indicate an association between pulmonary respiration and cutaneous mitoPO2 during physical exercise. The observed mitochondrial threshold, coinciding with the metabolic transition from an aerobic to an anaerobic state, might be of importance in critical care as well as in sports medicine.